EFEKTIVITAS POSISI PRONASI TERHADAP SATURASI OKSIGEN, FREKUENSI NADI, FREKUENSI NAFAS PADA BAYI PREMATUR DENGAN VENTILATOR - Priyo Budi Danu Nugroho; Ria Setia Sari; Febi Ratnasari (Nusantara Hasana Journal, 2023)
In Banten province, the incidence of premature mortality occurred from 9,7% to 10% and was ranked 15th indonesia and in tangerang regency the premature death rate was 138 cases in 2019 decreased by 120 cases in 2018. Purpose of this study to find out how the effectiveness of the pronation position on pulse rate, respiratory rate in premature infants with ventilators. The search for this research article through Google Scholar, Pudmed, and ResearchGade uses keywords and inclusion criteria within the period of the article from 2017-2021. There are 7 journals which related and results of matrix synthesis into 3 categories: input, process, and output. There are 4 effects of pronation positions, 3 comparisons of prone and supine positions. Based on several journals that have been reviewed, I conclude that there is an influence between the effectiveness of the pronation position on the pulse rate, respiratory rate, and oxygen saturation in infants using a ventilator.